The Theory of Didactic Situations and the Generalization of Pythagoras’ Theorem: An Experience Mediated by GeoGebra software - Renata Teófilo de Sousa; Maria Graciene Moreira dos Santos; Francisco Régis Vieira Alves (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: The objective of this work is to present the development of an activity on the Generalization of Pythagoras’ Theorem with the support of GeoGebra. Methodology: The methodology used was Didactic Engineering, in which we conducted a qualitative and exploratory analysis of the data. For the teaching session, we relied on the Theory of Didactic Situations. The activity was developed with 18 students from the 2nd year of high school at a Professional School in Sobral, Ceará, Brazil, in April 2023. The students were selected because they faced difficulties with the topic, identified through a school diagnostic assessment. Its implementation was an intervention by the teacher to understand these difficulties and clarify them with the support of GeoGebra. Findings: In the results, specific difficulties of the students were identified, and it was observed that the Generalization of Pythagoras’ Theorem via GeoGebra software was well-received by the group. Significance: It awakened their perception of the elements that make up a right triangle.